2005
DOI: 10.1021/cm0487122
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of Copper Phthalocyanine Films by Glow-Discharge-Induced Sublimation

Abstract: Copper phthalocyanine (CuPc) thin films have been deposited by a recently developed plasma-based method named glow-discharge-induced sublimation (GDS). The deposition of CuPc films has also been obtained by vacuum evaporation (VE) and the comparison of the two methods shows important structural differences. FT-IR and ion beam analyses (RBS-ERDA) show that the GDS-deposited films mainly consist of integer CuPc molecules, but at increasing deposition time the incorporation of damaged molecules becomes important.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 44 publications
(60 reference statements)
5
39
0
2
Order By: Relevance
“…770 and 780 cm s −1 absorption is ascribed to the vibrational mode of the central part of CuPc cycle for α CuPc and β CuPc, respectively. The other features are broad peaks at 864-870 cm s −1 for α CuPc and 877, 957, and 1100 cm s −1 β CuPc [10]. It can be clearly noted that the absorption observed in the present study is in agreement with the reported that of β CuPc phase, with a small shift to higher wavelength in all cases.…”
Section: -5 Nm For the Films Of Cupc Formed By The Present Methodsupporting
confidence: 91%
See 2 more Smart Citations
“…770 and 780 cm s −1 absorption is ascribed to the vibrational mode of the central part of CuPc cycle for α CuPc and β CuPc, respectively. The other features are broad peaks at 864-870 cm s −1 for α CuPc and 877, 957, and 1100 cm s −1 β CuPc [10]. It can be clearly noted that the absorption observed in the present study is in agreement with the reported that of β CuPc phase, with a small shift to higher wavelength in all cases.…”
Section: -5 Nm For the Films Of Cupc Formed By The Present Methodsupporting
confidence: 91%
“…This is an interesting observation since the starting CuPc was exclusively in α phase as observed by XRD. It is reported that the phase transition from metastable α phase to stable β phase occurs by heat treatment over 250 • C [10]. In the present method of film formation, the atmospheric temperature is maintained throughout the experimentation and therefore the observed phase transformation needs explanation.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…24 The FT-IR spectroscopy results further confirm the genuineness of the a-form of ZnPc NW as it displays a fingerprint-bending mode of C-H at 724 cm À1 together with the vibrational mode of the center cyclic ring at 773 cm À1 (Supplementary Figure S2). 25,26 Note that ZnPc NW samples are collected from multiple reaction batches for the PW XRD measurements.…”
Section: Resultsmentioning
confidence: 99%
“…Maggioni [143] propôs a utilização de dessorção por plasma para fins similares. No entanto, polimerização por plasma apresenta diversas vantagens uma vez que espécies ativas únicas são formadas no plasma e que normalmente favorecem a obtenção de novos materiais.…”
Section: Materiais Para Adsorção E Detecçãounclassified